VAMPIRE TRANSFORMATION: A COMPARATIVE STUDY OF THE NOVEL AND FILM DRACULA - Karim, Tuki Madani; Paturohmah, Pepi Siti; Priyawan, Pepen; Mansyur, Agus Salim (CALL, 2024)
This article aims to explore the intersection between comparative literature and adaptation studies, examining the theoretical frameworks and practical applications that underlie this fascinating field. By analysing the transformation of a classic work into various media, we will uncover the mechanisms of change and the cultural significance embedded in these adaptations. This article examines the film adaptation of Bram Stoker's novel Dracula by Francis Ford Coppola. A comparative analysis is conducted on the novel and film to identify significant changes that occurred in the adaptation process. These changes include the addition of scenes, character modifications, and changes to the plot. One of the main changes is the addition of a romantic element between Dracula and Mina, which is not present in the original novel. This change transforms the theme of gothic horror into a more nuanced tragic love story. The study concludes that the film adaptation of Bram Stoker's Dracula involves a number of significant changes that alter the meaning and experience of the narrative. Further research is needed to understand the motivations and impact of changes in the adaptation process, especially from a cultural and sociological perspective. In addition, a broader comparative study could be conducted by comparing different adaptations of Dracula to see the patterns of change that occur over time. It is also important to understand how changes in adaptation affect audience reception. Adaptation research methodology needs to be continuously developed by integrating digital humanities approaches and new technologies to provide a more comprehensive perspective. More systematic documentation of the decision-making process in adaptation is also needed to understand the factors that influence changes from novel to film, so as to provide deeper insight into the process of adapting literary works to visual media. Keyword: comparative literature, adaptation studies, transformation, character, plot